RISKS OF INCLUSIVE EDUCATION - M. R. Husnutdinova (Obrazovanie i Nauka, 2017)
Introduction. Inclusion is a new and unfamiliar phenomenon for most of the Russians which is treated as ensuring equal access to education for all students taking into account a variety of their special educational needs and individual capabilities. Inclusive educational model began to take root in Russia without a broad public debate and today’s parents and teachers were not ready to the cardinal changes caused by transition to the new model of education. In this regard, the studying of directly educational process by consequences of inclusive training and education is urgent now.The aims of the research are the following: to identify the major risks that characterize the current stage of the implementation process of inclusion in the Russian educational organizations; to consider the main causes that lead to their occurrence; to present a comparative analysis of the views of respondents in comprehensive, inclusive and correctional schools. Methodology and research methods. The Sector Monitoring Studies of Moscow State University of Psychology & Education in 2010 and 2014 implemented a sociological study on the process of introduction of inclusion in the Russian schools. 200 teachers and 244 parents were interviewed in 2010; in 2014, in addition, 178 teachers and 386 parents were interviewed; 47 senior students including those with disabilities were interviewed too.Results. According to the results, the main concerns of the parents of students of comprehensive, inclusive and correctional schools are reduced to a few basic risks: lack of individual approach while teaching children with different educational needs, increased emotional pressure on the child, and child’s perception of the complexity of disability as an equal. These risks arise primarily because of the acute shortage of especially prepared-governmental teachers and socio-cultural, psychological unpreparedness of most contemporary children with disabilities to the perception of them as classmates.Scientific novelty. For the first time, the author has made an attempt to: analyse a real situation of process of introduction of inclusive education is made; get a deep insight into the main participants of members of the general education; observe the dynamics of risks’ conceptions of inclusive education on the basis of systematization and generalization of the opinions recorded in recent years.Practical significance. The comparison of various positions concerning the status and prospects of inclusive education allows us to understand more precisely the existing problems and, therefore, to find the most effective ways of their decision.